Recycling of spodumene slag: preparation of green polymer composites. Issue 43 (14th April 2016) - Qiu, Yaxin; Wu, Defeng; Yan, Lili; Zhou, Ye
Abstract : The recycling of spodumene slag is studied in this work, with the objective of exploring the possibility of using spodumene slag as a common polymer filler. Abstract : Nowadays, spodumene ores have become an important lithium resource. The generated slag, as a new member of the slag family, would cause the environmental burden to mount up. Therefore, the recycling of spodumene slag was studied in this work, with the objective of exploring the possibility of using spodumene slag as a common polymer filler. The microsized slag powder was firstly incorporated with polylactide (PLA) through solution mixing, followed by injection molding, and the obtained composites were then studied in terms of morphology, rheological and mechanical properties, as well as the creep and degradation behavior. The results reveal that the presence of slag powder enhances the system modulus evidently, while maintaining the normal strength level of PLA. Therefore, the slag powder can be used as a good inert filler in the polymeric material industry, with a desirable reduction in cost. Then, the slag powder was further refined into nanoparticles, and again mixed with PLA. The results show that the presence of these nanoparticles increases both the modulus and strength remarkably because of their good dispersion and distribution in the PLA matrix. As a result, these spodumene slag-derived nanoparticles can be used as a good reinforcement material or as an active filler in the polymer additive industry. Both the slag powder and slag-derived nanoparticles highly restrain the creep of the PLA chain, while promoting the degradation of PLA remarkably. Therefore, these particles can be used to tailor the final properties of PLA. In addition, a modified model was developed successfully to predict the mechanical strength of the as-obtained green composites. This work provides a new way to fabricate a novel green polymer composite with controllable performance by the recycling of spodumene slag.